Time-averaged flow characterisations in a bimodal gravel-bed stream and relative role of sediment depositions on near-bed coherent flow structures - Ratul Das; Pritam Malakar; Akash Datta (Water Supply, 2024)
The present study aims to quantify experimentally the relative role of sediment depositions on near-bed flows and turbulence in a gravel-bed stream. Time-averaged velocity was measured over a sand-filled gravel-bed stream with four cases of sediment depositions and compared with those over a gravel-bed stream without sediment depositions. An acoustic Doppler velocimeter was used to measure the instantaneous velocity of flows. The progressive infilling of void spaces in the gravel-bed stream forms distinct bimodal depositions that alter the mean flows characterised by increasing zero-velocity levels and massive damping in the bed shear stresses. The data plots of turbulent intensity depict enhancement of streamwise turbulent intensity in the near-bed flow region with increasing sand depositions. Moreover, the opposite nature of streamwise and vertical turbulent kinetic energy fluxes in the interfacial sublayer leads to slowing down the time-average Reynolds shear stresses at the vicinity of the gravel-bed surface. At the vicinity of the crest, the ejection and sweep events contributed approximately 86 and 56%, respectively, to the total Reynolds shear stress production in the case of gravel bed under clear-water flow conditions. By contrast, the contributions of turbulent sweep events increased over the sand-filled gravel bed at the same location. HIGHLIGHTS Sediment particle entrainment and interstices within the pore spaces of a gravel bed.; Results are compared with the flows over an immobile gravel-bed stream under clear-water flow conditions.; A higher level of sand deposition depicts massive damping in the near-bed Reynolds shear stress profiles.;